The Relationship Between Self-Esteem and Social Support with Self-Confidence In High School / Vocational School Students Without A father Figure In Surabaya - Yasyfa Ainan Ramadhani; Dzulkifli; Iffah Rosyiana (P3I UMSurabaya, 2025)
This study aims to emphasize the importance of improving self-esteem and social support to strengthen the confidence of high school/vocational school students without a father figure in Surabaya. Using a quantitative approach with purposive sampling, this study involved 163 high school and vocational school students aged 15-18 years who did not have a father figure. The instruments consisted of validated and reliable scales that measured self-esteem, social support, and self-confidence. The analysis revealed a significant relationship between self-esteem and self-confidence, as well as between social support and self-confidence in high school/vocational school students without a father figure in Surabaya. Multiple correlation analysis indicated a very strong combined influence of self-esteem and social support on self-confidence in high school/vocational school students without a father figure in Surabaya.